2016
DOI: 10.18805/ajdfr.v35i4.6623
|View full text |Cite
|
Sign up to set email alerts
|

Studies on physico-chemical properties of skim milkpowder sold in Maharashtra

Abstract: Twenty five market skim milk powder samples obtained from various regions of Maharashtra were analysed for their chemical composition, physico-chemical properties and microbiological quality to access their suitability in terms of national and international standards. It was observed that the moisture, fat, protein, lactose and ash content of SMP samples obtained from various regions showed significant difference (P<0.05). It was also revealed that the scorched particle content, solubility index, dispersibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
3
0
0
Order By: Relevance
“…The mean values of moisture, %, TS, %, fat, %, protein, %, and titratable acidity, %, were 3.77 ±0.08, 96.25 ±0.08, 1.11 ±0.05, 34.62 ±0.29 and 1.22 ±0.03 for the examined dry skim milk samples, respectively. The compositional parameters of the examined skim milk powders were almost identical to those reported by Patil et al (2016).…”
Section: Statistical Analysis Of the Compositional Parameters For The Examined Milk Powder Samplessupporting
confidence: 80%
“…The mean values of moisture, %, TS, %, fat, %, protein, %, and titratable acidity, %, were 3.77 ±0.08, 96.25 ±0.08, 1.11 ±0.05, 34.62 ±0.29 and 1.22 ±0.03 for the examined dry skim milk samples, respectively. The compositional parameters of the examined skim milk powders were almost identical to those reported by Patil et al (2016).…”
Section: Statistical Analysis Of the Compositional Parameters For The Examined Milk Powder Samplessupporting
confidence: 80%
“…These results agree with Alcantara et al (2013); Panyoo et al (2013); Himeda et al (2014) whose found that the content of protein ranged 2.0-8.07%, fat 0.2-1.0, ash 0.2-2.7%.SMP contained 3.80, 36.00, 1.25, 8.20 and 50.75% moisture, protein, fat, ash and carbohydrate, respectively. These results are in line with Patil et al (2016) and Pugliese et al (2017) whose found that, the skimmed milk powder composed from 1.1-4.2%, 31.91-39.8, 0.2-1.56 and 7.4-8.5% moisture, protein, fat and ash, respectively. Finally, taro flour had the lowest content of fat compared to other components and the protein content of taro was higher than wheat flour.…”
Section: Chemical Composition Of Some Raw Materials Used In Chicken Nusupporting
confidence: 90%
“…Most of the proximate values reported in this study do not differ from the findings of Cucurbitaceae seed protein isolates reported by Wani et al 15 The energy values of the SMP and WSPI were significantly different with a lower (363.94 kcal) calorific value for WSPI. Present research showed that proximate composition (other than protein and carbohydrates) of WSPI was within the range of the earlier reported values of SMP 51,52 and may be used for replacement in chocolate and other confectionary products.…”
Section: Yield and Physical Characteristics Of Wspisupporting
confidence: 88%